Mitigating Climate Change in Africa: Barriers to Financing Low-Carbon Development - Adenle, Ademola A.; Manning, Dale T.; Arbiol, Joseph (World development, 2017)
•Lack of institutional capacity limits the implementation of mitigation actions in Africa.•Fewer implementation of GEF-financed mitigation projects is due to lower institutional capacity.•Establishing a regional institution is key to filling the existing institutional gaps in the continent. Meeting global climate change mitigation goals requires the participation of developing countries in abatement programs to encourage low-carbon development pathways. Incentivizing developing countries to participate in climate change mitigation often requires a mechanism for developed countries to finance projects in poorer countries. While several funding institutions have been established, African country participation has been low. In this analysis, we conduct interviews with climate change policy stakeholders from across the continent and find a general consensus that a lack of institutional capacity has limited the participation of African countries in existing climate change mitigation programs. To confirm this qualitative observation, we use data from the Global Environment Facility (GEF) and the World Bank to examine the correlation between country-year measures of institutional capacity and the number of projects implemented by the Global Environment Facility (GEF) and find that better institutional quality is associated with more GEF projects implemented in a country-year. We propose to address the lack of institutional capacity with the creation of regional institution, or Climate Change Mitigation Institution (CCMI), that specializes in building local capacity by leveraging external capacity as well as facilitates the integration of African countries into global climate change mitigation efforts by improving capacity, strengthening research and development, forming partnerships, and coordinating the disbursement of financing.